MARKETING STRATEGY OF TRADITIONAL MARKET TRADERS TOWARDS MODERN MARKETS IN MMTC - Br Purba, Marissa Avina; simarmata, eprimanta; manurung, ahmad ismail; akbar, dony (Academic Solution Publisher, 2024)
In Indonesia, markets can be categorized into two primary types: modern markets and traditional markets. Contemporary markets encompass expansive shopping centers, minimarkets, supermarkets, and malls, whereas traditional markets consist of local markets, street vendors, and micro enterprises. While both types of markets play a significant role in the economy, modern markets evolve at a quicker pace than traditional markets. The proximity of modern markets to traditional markets and small retail businesses generates a notable economic influence on the surrounding environment. Changes in consumer behavior patterns represent a significant impact. Consumers in contemporary markets are increasingly transitioning their shopping preferences from traditional venues to modern establishments, which provide enhanced convenience and a broader range of products. Qualitative research employs data collection methods that are often unstructured and adaptable, including in-depth interviews, participant observation, and focus group discussions. The approach employed by conventional traders in the mmtc market to promote their products involves direct promotions and effective communication, which positively influences traders and facilitates various aspects for consumers. Traders who maintain a welcoming demeanor tend to attract a larger customer base, as their quality service encourages consumers to purchase their products.